2020
DOI: 10.2147/cmar.s272478
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hsa_circ_0084927 Regulates Cervical Cancer Advancement via Regulation of the miR-634/TPD52 Axis</p>

Abstract: Background: Cervical cancer (CC) is a common gynecological tumor that affects women's health. Circular RNA hsa_circ_0084927 (hsa_circ_0084927) has been reported to be upregulated in CC. However, the role and regulatory mechanism of hsa_circ_0084927 in CC are unclear. Methods: Expression of hsa_circ_0084927, microRNA (miR)-634, and tumor protein D52 (TPD52) mRNA in CC tissues and cells was examined by quantitative real-time polymerase chain reaction (qRT-PCR). The proliferation, colony formation, cell cycle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In CC, circRNA_0023404 has been proved to serve as an oncogenic regulator by affecting the miR-136/YAP axis [11] and circHIPK3 promoted the progression of CC via modulating the miR-485-3p/FGF2 axis [12]. In addition, the circ_0007364/miR-101-5p/MAT2A axis and circ_0084927/miR-634/TPD52 axis were also found in the development of CC [13,14]. Circ_0007534 is derived from DEAD box polypeptide 42 (DDX42) gene in the chr17: 61869771-61877977, and it has been identified as a carcinogene in many types of cancers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In CC, circRNA_0023404 has been proved to serve as an oncogenic regulator by affecting the miR-136/YAP axis [11] and circHIPK3 promoted the progression of CC via modulating the miR-485-3p/FGF2 axis [12]. In addition, the circ_0007364/miR-101-5p/MAT2A axis and circ_0084927/miR-634/TPD52 axis were also found in the development of CC [13,14]. Circ_0007534 is derived from DEAD box polypeptide 42 (DDX42) gene in the chr17: 61869771-61877977, and it has been identified as a carcinogene in many types of cancers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As shown by the result, the expression of TPD52 was greatly down‐regulated upon circ_0060551 silencing while no obvious change was observed in that of CLDN4. Moreover, as it has been reported that circ_0084927 up‐regulates TPD52 to promote the progression of cervical cancer, 18 TPD52 was determined as the downstream mRNA of circ_0060551. Then, TPD52 was detected to be significantly up‐regulated in CC cells (Figure 3J).…”
Section: Resultsmentioning
confidence: 99%
“… 22 Hsa_circ_0084927 promotes the progression of CC by up-regulating TPD52 via sponge adsorption of miR-634, which provides new evidence for its use as a promising therapeutic target. 23 The significantly high expression in these tumors suggests that they may have potential cancer-promoting possibilities, which are worthy of further study. Up to now, there is very little research on hsa_circ_0084927, and more importantly, the function and mechanism of hsa_circ_0084927 have not been fully studied, and its role in tumor is unclear.…”
Section: Discussionmentioning
confidence: 98%